Assessment of dopaminergic neuron degeneration in a C. elegans model of Parkinson's disease - Palikaras, K.; SenGupta, T.; Nilsen, H.; Tavernarakis, N. (STAR Protoc, 2022)
Transgenic Caenorhabditis elegans that expresses the full-length wild-type human alpha-synuclein in dopaminergic neurons provides a well-established Parkinson's disease (PD) nematode model. Here, we present a detailed protocol to monitor and dissect the molecular underpinnings of age-associated neurodegeneration using this PD nematode model. This protocol includes preparation of nematode growth media and bacterial food sources, as well as procedures for nematode growth, synchronization, and treatment. We then describe procedures to assess dopaminergic neuronal death in vivo using fluorescence imaging. For complete details on the use and execution of this protocol, please refer to SenGupta et al. (2021).
Palikaras, KonstantinosSenGupta, TanimaNilsen, HildeTavernarakis, NektariosengResearch Support, N.I.H., ExtramuralResearch Support, Non-U.S. Gov'tSTAR Protoc. 2022 Mar 31;3(2):101264. doi: 10.1016/j.xpro.2022.101264. eCollection 2022 Jun 17.
Keywords: *Caenorhabditis elegans Proteins; *Cell Biology; *Model Organisms; *Molecular Biology; *Neuroscience; *Parkinson Disease/genetics; Animals; Caenorhabditis elegans; Disease Models, Animal; Dopamine; Dopaminergic Neurons; Humans